Manajemen Krisis Event Organizer Xcreative Dalam Mengembalikan Kepercayaan Publik: (Studi Kasus Pembubaran Acara Festival Musik Bertajuk “i’Fest sing a long ga si” 2021) - Tio Gunarsyah; Yulanda Trisula Sidarta Yohanes; Asrin Dimas Tri Fathullah; Dian Lestari Miharja (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
ABSTRACT Crisis management is an organization's efforts to overcome a crisis. Efforts in crisis management are carried out in stages and through various activities. Companies or organizations must be able to make decisions in a short time regarding what must be done immediately as a crisis management effort. Crisis management can be interpreted as a form of response and effort to respond to and solve crisis problems that arise through possible crisis management strategies. Crisis management is different from risk management which involves an element of assessing potential threats as well as the best way to avoid threats, meaning that this action is carried out before an event (risk) happen. Crisis management is actually carried out when a threat or crisis event occurs. This research aims to find out how Xcreative Organizer's crisis management can restore public trust. This research uses a qualitative research method with a descriptive approach with research subjects being stakeholders at Xcreative Organizer. The object of this research is the Event Organizer's crisis management in restoring public trust. Researchers used unstructured interview methods and documentation to obtain data. The data analysis technique in this research uses data analysis techniques according to Miles and Huberman with steps, data reduction, data presentation and drawing conclusions. The data validity test uses data source triangulation techniques. In this research, it was found that Xcreative Organizer applied Situational Crisis Communication Theory and Crisis Response Strategy in its crisis management. Crisis management can be an effort to restore public trust and restore image. Keywords: Crisis Management, Event Organizer, Return of Truth